The Knowledge and Effects of Teenage Pregnancies Among the Adolescent Girls Between 13 To 19 Years at Mukono Parish Kanungu District – Uganda. - Nkabura, Hubert (Student's Journal of Health Research Africa, 2020)
Background: Teenage pregnancy prevalence is at 25%, 16% of Ugandan women are married by the age of 15 years, and 53% by the age of 18 years. Available information reveals that teenage pregnancies carry a higher health risk and girls under 15 years are five times more likely to die in childbirth than females in their twenties. An estimate of 6,000 teenagers dies annually from maternal related complications. Methodology: A descriptive cross-sectional study was conducted in February 2016 where a total of 100 respondents were selected from Mukono Parish residents’ register using a simple random sampling technique. Data was collected using a pretested questionnaire. Results: 76% had prior knowledge about sex education whereas 24% had not. 42% got the information from the school a gesture that respondents took part in the classroom discussion about sexuality, 28% from newspapers –straight talk, 16% health worker, and 14% from their parents. 45% believed that school dropout is due to social effect of teenage pregnancy, 34% said that teen mother is more likely to have no or low qualifications and 9% said that child of a teen mother is more likely to abuse drugs, 12% don’t know any of the social effects. Conclusion and recommendations: Teenagers in Uganda are informed about sex education. The government in conjunction with the development partners needs to include sex education in the school curriculum. The girl child needs to be educated on how to protect herself and avoid becoming a victim of teenage pregnancy. Parents should not shy away from educating their children about sex education while they are still young, by so doing the teens grow knowing the consequences of early pregnancy. Pregnant teenagers need to be encouraged to attend antenatal care as well as welcomed into society without stigmatization.